Interactions Between phyB and PIF Proteins Alter Thermal Reversion Reactions in vitro. (21st July 2017) - Smith, Robert W.; Helwig, Britta; Westphal, Adrie H.; Pel, Eran; Borst, Jan Willem; Fleck, Christian
Abstract: The dynamic behavior of the plant red/far‐red light photoreceptor phytochrome B (phyB) has been elucidated in natural and synthetic systems. Red light switches phyB from the inactive Pr state to the active Pfr state, a process that is reversed by far‐red light. Alongside light signals, phyB activity is constrained by thermal reversion (that is prominent in the dark) and protein–protein interactions between phyB, other phytochrome molecules, and, among others, PHYTOCHROME INTERACTING FACTORs (PIFs). Requirements for phyB‐PIF association have been well studied and are central to light‐regulated synthetic tools. However, it is unknown whether PIF interactions influence transitions of phyB between different conformers. Here, we show that the in vitro thermal reversion of phyB involves multiple reactions. Thermal reversion of phyB in vitro is inhibited by PIF6, and this effect is observed at all temperatures tested. We analyzed our experimental data using a mathematical model containing multiple Pfr conformers, in accordance with previous findings. Remarkably, each Pfr conformer is differentially regulated by PIF6 and temperature. As a result, we speculate that in vivo phytochrome signaling networks may require similar levels of complexity to fine‐tune responses to the external environment. Abstract : The red/far‐red light plant photoreceptor phytochrome B (phyB) interacts with PHYTOCHROME INTERACTING FACTOR (PIF) proteins to regulate downstream responses in both natural and synthetic systems. Here, we show that the interaction with PIF proteins inhibits the thermal reversion of phyB from the active Pfr to inactive Pr state across the ambient temperature range. In combination with mathematical modelling, we determine that two forms of Pfr exist, that they have different thermal relaxation rates, and that they are differentially regulated by PIFs. Further unknown biological modifications to the phyB‐PIF complexes ultimately prevent thermal reversion of phyB.